2000
DOI: 10.1590/s0036-46652000000200006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response in cattle after vaccination with inactivated and attenuated rabies vaccines

Abstract: SUMMARYDespite the absence of current official reports showing the number of cattle infected by rabies, it is estimated that nearly 30,000 bovines are lost each year in Brazil. In order to minimize the important economic losses, control of the disease is achieved by eliminating bat colonies and by herd vaccination. In this study, we compare the antibody response in cattle elicited by vaccination with an attenuated ERA vaccine (AEvac) and an inactivated-adjuvanted PV (IPVvac) vaccine. The antibody titers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
2
9
1
4
Order By: Relevance
“…By the end of the study, rabies antibody titers had decreased in most of the groups (Figure 2), as expected for primo-vaccinated cattle (30)(31)(32)(33)(34). In contrast, these antibody titers were sustained in group G 3.6 that received selenium supplementation close to 3 mg/day, the dose recommended by the NRC for taurine breeds (23).…”
Section: Introductionsupporting
confidence: 72%
“…By the end of the study, rabies antibody titers had decreased in most of the groups (Figure 2), as expected for primo-vaccinated cattle (30)(31)(32)(33)(34). In contrast, these antibody titers were sustained in group G 3.6 that received selenium supplementation close to 3 mg/day, the dose recommended by the NRC for taurine breeds (23).…”
Section: Introductionsupporting
confidence: 72%
“…However, single doses of rabies vaccines have been associated with low levels of neutralizing antibodies and also with occurrence of disease in vaccinated animals (9,15). On the other hand, the use of a booster has significantly increased antibody specific levels (2,6,10,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…Among them (discussed in detail by Zanetti et al1998, Rodrigues da Silva et al 2000 a point that must be raised is the fact that, because rabies vaccines are officially controlled in Brazil by tests performed on laboratory animals (mice or guinea-pigs), it is always questionable whether the minimal mandatory requirements for a vaccine being approved really correspond to high immunogenicity in the target species. We have recently reported that an attenuated ERA vaccine officially approved by the LARA evoked very low and transient titers of neutralizing antibodies in cattle (Rodrigues da Silva et al 2000). Another point to be stressed is the importance of the content of rabies glycoprotein (G) in the vaccine.…”
mentioning
confidence: 99%